2000
DOI: 10.1016/s0014-5793(00)02295-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FAK‐associated signaling pathways in the regulation of cell cycle progression

Abstract: Focal adhesion kinase (FAK) is an important mediator of signal transduction pathways initiated by integrins in cell migration, survival and cell cycle regulation. The ability of FAK to mediate integrin signaling in the regulation of cell cycle progression depends on the phosphorylation of Tyr397, which implies a functional significance for the formation of FAK signaling complexes with Src, phosphatidylinositol-3-kinase (PI3K) and Grb7. We have previously described a FAK mutant, D395A, that selectively disrupts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 33 publications
0
39
0
1
Order By: Relevance
“…There are no reports which suggest a role for Grb7 in the regulation of cell proliferation. Indeed, our laboratory has shown recently that overexpression of the Grb7 SH2 domain does not decrease cell cycle progression (Reiske et al, 2000), although it inhibited cell migration under similar conditions (Han and Guan, 1999). These results suggest that Grb7 family members may play di erent roles in various cellular functions such as cell proliferation and migration.…”
Section: Roles In Cell Proliferation and Apoptosismentioning
confidence: 93%
“…There are no reports which suggest a role for Grb7 in the regulation of cell proliferation. Indeed, our laboratory has shown recently that overexpression of the Grb7 SH2 domain does not decrease cell cycle progression (Reiske et al, 2000), although it inhibited cell migration under similar conditions (Han and Guan, 1999). These results suggest that Grb7 family members may play di erent roles in various cellular functions such as cell proliferation and migration.…”
Section: Roles In Cell Proliferation and Apoptosismentioning
confidence: 93%
“…FAK Phosphorylation-Recruitment of p125 FAK to focal contacts results in its activation through the phosphorylation of tyrosine residues (40). We compared the level of p125 FAK protein as well as its activity between Swiss 3T3 and LA1 cells.…”
Section: Mmp Inhibitors Promote P125mentioning
confidence: 99%
“…However, identification of the constituents of FAK signaling complexes that regulate proliferation and/or migration signals and the relative contributions of these distinct complexes toward these cellular processes is poorly understood and is an area of intense investigation. Recently, Reiske et al (2000) and Oktay et al (1999) reported that the formation of a FAK/Src complex and interaction with p130 CAS are required for the regulation of cell-cycle progression by FAK. Conversely, Xie et al (2001) have reported that FAK can associate with signal transducer and activator of transcription-1 (STAT-1) and that this signaling complex can promote cell migration.…”
Section: Antisense Targeting Of Fak Reduces Mmp2 Activitymentioning
confidence: 99%
“…FAK plays a key role in regulating cytoskeletal organization, gene expression, and cell behavior such as cell spreading and migration (Hanks and Polte, 1997). In addition, FAK may also have a role in regulating the G1 to S phase transition of the cell cycle (Reiske et al, 2000;Zhao et al, 1998) and the suppression of anoikis (Frisch et al, 1996;Hungerford et al, 1996;Ruoslahti and Reed, 1994;Xu et al, 1996).…”
mentioning
confidence: 99%